Stiffness Adjustment Analysis of Continuous Origami Manipulators - Zhang Yuhui; Zhang Fan (Jixie chuandong)
Aiming at the stiffness adjustment of the continuous manipulator designed by the deformed Miura origami mechanism, the influence of geometric parameters on the stiffness of the origami robot arm is discussed. Firstly, based on the bar-and-hinge model method, the taper angle and length of the three sets of origami robot models are maintained, pressure is applied to the robot arm, the bending stiffness of the manipulator in the state of extension and contraction is analyzed by the Matlab simulation program, and the corresponding bending stiffness ratio is calculated. The results show that when the number of edges of the polygon on the end face of the manipulator is increased from 5 to 7, the bending stiffness ratio increases with the increase of the number of polygon edges, so that the origami manipulator is rigid and flexible in the state of extension. Secondly, the force-displacement relationship of the origami manipulator is further modeled using the principle of virtual work, the relationship between the cone angle and the load force of the manipulator is clarified, and the three groups of origami manipulators with different cone angles are also analyzed. Finally, a conclusion is drawn that with the increase of the cone angle, the resistance to external forces is not always increasing. That is, the change of the cone angle has an impact on the load performance of the manipulator.